A Grounded Theory of the Practice of Disaster Spiritual and Emotional Care: The Central Role of Practical Presence - Schruba, Alice N. (Journal of psychology and christianity, 2018)
The purpose of this qualitative study was to develop a grounded theory explaining how disaster spiritual and emotional care (DSEC) providers actually practice DSEC in the field. Fourteen peer-nominated, exemplar DSEC providers completed a semistructured interview, and a grounded theory approach (Corbin & Strauss, 2015; Glaser & Strauss, 1967) was used to analyze the data. The central theme emerging from the data and the key component of how DSEC is practiced is what providers called "practical presence" (i.e., meeting survivors' immediate practical needs while being physically, emotionally, and spiritually present in ways that facilitate survivors' holistic health and well-being). Participants described the characteristics of this practical presence within the DSEC context, as well as the process by which they (a) prepared for offering practical presence, (b) offered practical presence in microlevel DSEC (to individuals and families), and (c) offered practical presence in macrolevel DSEC (to communities). We discuss implications for the provision of DSEC and offer recommendations for future research.